Degeneration in the ventral cochlear nucleus after severe noise damage in mice - Feng, J; Bendiske, J; Morest, D K (Journal of Neuroscience Research, 2012)
To study the mechanisms of noise-induced hearing loss and the phantom noise, or tinnitus, often associated with it, we used a mouse model of noise damage designed for reproducible and quantitative structural analyses. We selected the posteroventral cochlear nucleus, which has shown considerable plasticity in past studies, and correlated its changes with the distribution of neurotrophin 3 (NT3). We used volume change, optical density analysis, and microscopic cluster analysis to measure the degeneration after noise exposure. There was a fluctuation pattern in the reorganization of nerve terminals. The data suggest that the source and size of the nerve terminals affect their capacity for regeneration. We hypothesize that the deafferentation of ventral cochlear nucleus is the structural basis of noise-induced tinnitus. In addition, the immunofluorescent data show a possible connection between NT3 and astrocytes. There appears to be a compensatory process in the supporting glial cells during this degeneration. Glia may play a role in the mechanisms of noise-induced hearing loss. © 2011 Wiley Periodicals, Inc.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-539-907-848-327 tex.type: [object Object]
Keywords: Analysis of Variance; Animals; Calcium-Binding Proteins; Cluster Analysis; Cochlea; Cochlear Nucleus; Disease Models; Animal; Excitatory Amino Acid Transporter 2; Hearing Loss; Sensorineural; Hearing loss; Membrane Glycoproteins; Mice; Mice; Inbred C57BL; Mouse model; NT3; Nerve Growth Factors; Nerve Tissue Proteins; Neurodegenerative Diseases; Noise; Time Factors; Tinnitus; animal cell; animal experiment; animal model; animal tissue; article; astrocyte; controlled study; deafferentation; dept.bio; disease severity; environmental exposure; glia cell; hearing loss; immunofluorescence; mouse; nerve cell plasticity; nerve degeneration; nerve ending; nerve regeneration; neurotrophin 3; noise; nonhuman; optical density; posteroventral cochlear nucleus; priority journal; quantitative analysis; tinnitus

A taxonomic and biostratigraphic re-evaluation of the Post Quarry vertebrate assemblage from the Cooper Canyon Formation (Dockum Group, Upper Triassic) of southern Garza County, western Texas - Martz, Jeffrey W.; Mueller, Bill D.; Nesbitt, Sterling J.; Stocker, Michelle R.; Parker, William G.; Atanassov, Momchil N.; Fraser, Nicholas C.; Weinbaum, Johnathan; Lehane, James R. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
The Post Quarry, within the lower part of the type section of the Upper Triassic Cooper Canyon Formation in southern Garza County, western Texas, contains a remarkably diverse vertebrate assemblage. The Post Quarry has produced: the small temnospondyl Rileymillerus cosgriffi; the metoposaurid Apachesaurus gregorii; possible dicynodonts and eucynodonts; a clevosaurid sphenodontian; non-archosauriform archosauromorphs (Trilophosaurus dornorum, simiosaurians, and possibly Malerisaurus); the phytosaur Leptosuchus; several aetosaurs (Calyptosuchus wellesi, Typothorax coccinarum, Paratypothorax, and Desmatosuchus smalli); the poposauroid Shuvosaurus inexpectatus (Chatterjeea elegans); the rauisuchid Postosuchus kirkpatricki; an early crocodylomorph; several dinosauromorphs (the lagerpetid Dromomeron gregorii, the silesaurid Technosaurus smalli, a herrerasaurid, and an early neotheropod); and several enigmatic small diapsids. Revised lithostratigraphic correlations of the lower Cooper Canyon Formation with the Tecovas Formation, the occurrence of Leptosuchus, and the overall composition of the assemblage indicate that the Post Quarry falls within the Adamanian biozone, and not the Revueltian biozone. Stratigraphic subdivision of the Adamanian biozone may be possible, and the Post Quarry may be correlative with the upper part of the Adamanian biozone in Arizona. The age of the Post Quarry assemblage is possibly late Lacian or earliest Alaunian (late early Norian or earliest middle Norian), between 220 and 215 Ma. © 2013 The Royal Society of Edinburgh.
28 citations (Crossref) [2023-10-31] Citation Key Alias: pop00103 tex.type: [object Object]
Keywords: Adamanian biozone; Dinosauromorpha; Garza County; Leptosuchus; Pseudosuchia; Texas; Triassic; United States; biostratigraphy; biozonation; dept.bio; faunal diversity; fossil assemblage; land vertebrate faunachrons; stratigraphic correlation; taxonomy; type locality; vertebrate; vertebrate locality

A survey of skeletal elements in the orbit of Pseudosuchia and the origin of the crocodylian palpebral - Nesbitt, Sterling J.; Turner, Alan H.; Weinbaum, Jonathan C. (Earth and Environmental Science Transactions of The Royal Society of Edinburgh, 2012)
14 citations (Crossref) [2023-10-31] Citation Key Alias: pop00106 tex.type: [object Object]
Keywords: Aetosaurus ferratus; Archosauria; Crocodylomorpha; Postosuchus kirkpatricki; Saurosuchus galilei; crocodilian; dept.bio; evolution; extinction; fossil assemblage; novelty; skeletal remains; supraorbital; taxonomy

The long journey of stem cell therapeutics. - Crawford, Sarah (Genome Medicine, 2012)
A report on the Euroepistem 2011 meeting 'Epigenomic Programming and Stem Cells for Drug Discovery', Paris, France, 21-22 November 2011.
0 citations (Crossref) [2023-10-31] Place: England Crawford, Sarah. Cancer Biology Research Laboratory, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. crawfords2@southernct.edu.
Keywords: Article; dept.bio; embryonic stem cell; epigenetics; gene; gene silencing; human; induced pluripotent stem cell; nonhuman; priority journal; stem cell transplantation; transcription regulation